2023
DOI: 10.1177/14705931221148514
|View full text |Cite
|
Sign up to set email alerts
|

Liminal consumption within Nigerian wedding rituals: The interplay between bridal identity and liminal gatekeepers

Abstract: This article combines the theoretical lenses of bridal identity and liminal consumption to illustrate the processes of problem-solving, negotiation and reconciliation through which the bride creates her bridal identity, in the Global South context of Nigeria. Most wedding ritual studies typically emphasise the processes of creating and negotiating a successful bridal identity, but few acknowledge the possibilities of failure and its effect upon the liminars. In addition, within liminal consumption studies, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 71 publications
0
3
0
Order By: Relevance
“…At the point of marriage or a long‐term committed relationship, the religious beliefs of two individuals are intermingled, sometimes merging and other times creating a permanent conflict point in a relationship (Perry, 2015). This is also the time period when consumption practices change (Fagbola et al, 2023), household size changes (Bongaarts, 2001), and household lifestyle is shaped with development of common living goals, habits, and consumption patterns (Du & Kamakura, 2006). Given that religious values are one of the most strongly held value systems for consumers (Mathras et al, 2016; Minton & Kahle, 2014), it is reasonable to expect strong influences of religious combining (or not) on marital adjustment, marital happiness, and consensual decision making.…”
Section: Religion and The Life Course Paradigmmentioning
confidence: 99%
“…At the point of marriage or a long‐term committed relationship, the religious beliefs of two individuals are intermingled, sometimes merging and other times creating a permanent conflict point in a relationship (Perry, 2015). This is also the time period when consumption practices change (Fagbola et al, 2023), household size changes (Bongaarts, 2001), and household lifestyle is shaped with development of common living goals, habits, and consumption patterns (Du & Kamakura, 2006). Given that religious values are one of the most strongly held value systems for consumers (Mathras et al, 2016; Minton & Kahle, 2014), it is reasonable to expect strong influences of religious combining (or not) on marital adjustment, marital happiness, and consensual decision making.…”
Section: Religion and The Life Course Paradigmmentioning
confidence: 99%
“…Both groom and bride's families are expected to spend huge amount of money throughout the wedding events to demonstrate their social and economic status. 7 In his study of changes forms of weddings in Nigeria, Fagbola (2019) found that weddings in Nigeria, among Muslims and Christians has been affected by the influence of Western culture where groom and bride spend an exorbitant among of money in the wedding processes. The researcher adopted a Netnographic approach in his study which concluded that the groom are expected to spend money in organizing lavish wedding parties as a mark of his social status and economic class.…”
Section: Sketch Of Literature Reviewmentioning
confidence: 99%
“…Third, we provide an integrative framework of consumers’ digital practice styles for well-being in liminal spaces (WILS) and argue that understanding liminality provides a sound basis for better understanding the intricacies of transformation in liminal service experiences. This focus on liminality in service contexts deepens the understanding of liminality, as research on liminality in marketing typically focuses on possessions, rituals and the consumption of goods (Darveau and Cheikh‐Ammar, 2021; Fagbola et al , 2023; Thomsen and Sørensen, 2006; Wells et al , 2023). Finally, we contribute managerial implications by way of insights into maternity health-care providers supporting women during the first stages of adaptation to motherhood.…”
Section: Introductionmentioning
confidence: 99%